SKRINING DAN PENGENDALIAN FAKTOR RISIKO IBU HAMIL DENGAN PELAYANAN ANTENATAL CARE TERPADU DI WILAYAH KERJA PUSKESMAS KECAMATAN MUARA KABUPATEN TAPANULI UTARA - Juana Linda Simbolon; Sulastry Pakpahan (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2020)
Background: The maternal mortality rate (MMR) in Indonesia is still quite high,based on the results of SUPAS in 2015, the MMR was 305/ 100,000 live births.Efforts to decrease of MMR can be done by ensuring that every mother can access quality health services for pregnant women because every pregnancy has the risk of complications. Integrated antenatal services are carried out including health counseling, antenatal care, case management and follow-up, preparation for delivery and planning for referrals in case of pregnancy. In the initial researchconducted in Hutaginjang Village, Muara, there were still pregnant women who did not have their pregnancy checked according to the minimum pregnancy standards. Purpose: Screening and pregnancy risk factors is indispensable for early pregnancy and the potential for emergency pregnancy. Methods: Activities carried out by integrated and free pregnancy examinations for pregnant women include measuring weight / height and arm  ircumference, vital signs, physical examination, Hb examination, urine protein and glucose, provision of IEC about nutritional fulfillment, overcoming complaints of pregnant women in trimester IIII,preparation for delivery and administration of iron supplements as well as preparation for referrals for mothers who experience complications in their pregnancy. Results: The activity was carried out without any obstacles, with 18 mothers having their pregnancies checked. The results of the examination found several risk factors for pregnancy, namely age under 20 years and above 35 years of parity, history of delivery by sectio, height below 145 cm, anemia,preeclampsia, breech location, hyperemesia gravidarum, gestational diabetes and gemelli pregnancy. Each mother received communication, information and education related to  maintaining and improving health during pregnancy and  giving iron tablets. Conclusion:Screening and control of pregnancy risk factors is needed to detect early whether the pregnancy is at risk and has the potential for emergency pregnancy, so that the mother can pass her pregnancy well and give birth to a healthy baby.